Consideration of industry markets development within enterprise anti-crisis management - Khatser, Maxim (Management and Entrepreneurship: Trends of Development, 2023)
The article is dedicated to forming new scientific solutions for improving anti-crisis management at Ukrainian enterprises, considering the development of industry markets, where business entities carry out financial, economic, and operational activities. It has been proven that in the contemporary economic landscape of our country, the development and implementation of anti-crisis management within domestic enterprises is essential. The article aims to create a set of measures to optimize the development and implementation of anti-crisis management at enterprises in Ukraine, considering the features of industry markets (markets of goods and resources) in which business entities carry out financial, economic, and operational activities. Methodology: a set of general and special methods has been used at the empirical and theoretical levels, such as the abstraction method for shaping terms definition “anti-crisis management at an enterprise,” “industry market (the market of goods and resources”)”; methods of analysis and synthesis to build a set of activities to optimize development and implementation of anti-crisis management at Ukrainian enterprises; a comparison method for specification of anti-crisis management measures for different groups of enterprises (industry leader, industry pursuer/persecutors, industry followers, and “niche” enterprises); methods of systematization, grouping and logical generalization for information systematization, formation of conclusions and scientific proposals of the article. The article uses system and functional, historical, and systemic approaches in revealing and solving the problems of improving anti-crisis management at enterprises of Ukraine, taking into account the development of industry markets (markets of goods and resources). Results: directions for optimizing anti-crisis management at Ukrainian enterprises have been identified, considering the development of industry markets in which business entities carry out financial, economic, and operational activities. JEL класифікатор: D 21, L10, M21